Measures of Residential Energy Access in Mexico, 2008–2014 - Perez, Rafael; Widner, Benjamin (Economics and Business, 2021)
The concept of energy access in developing countries, such as Mexico, encompasses the accessibility to reliable fuels for heating, cooking, and lighting purposes while reducing coal and firewood consumption. This paper suggests residential energy access indicators by applying accessibility theory and estimating demand equations for electricity, natural gas, propane, firewood, and coal using Mexican households’ survey data from 2008 to 2014. Sprawl measures, gravity model, and central place theory are the accessibility theories supporting the accessibility indicators. The suggested energy access indicators are statistically significant and show the expected signs when applied to propane in Mexican households in 2014. The greater the household income, population size, education level of the household head, energy access, and the lower the energy price and the household size, the greater the demand for energy from 2008 to 2014. By contrast, the greater the education, the lower the demand for firewood and coal. Policy-makers in Mexico can use the suggested results to complement the energy access indicators suggested by international agencies to evaluate energy access performance and better understand the drivers of the different energy goods consumed by Mexican households.